Pengembangan Sistem Pendeteksi Gesture Angka pada Tangan secara Realtime Berbasis Android - Wulandari, Pradipta Sekar Ayu Putri; Martono, Kurniawan Teguh; Windasari, Ike Pertiwi (Jurusan Teknik Elektro Universitas Negeri Semarang, 2020)
The Image Processing technology growing very rapidly now days. Many research develop this system. Cause image processing system can help deaf communication. Communication is a very important basic in life. Based on health profile in 2005 from Indonesian Ministry of health, the Indonesian congenital deafness reached 214.100 people. The congenital deafness is a hearing loss since birth, which lack of nerve impulses in the ear to convert the mechanical energy of vibration into electrical energy. With translator applications from sign languages to text, the deafness will be facilitated to interacting with other, despite the person can’t understand sign languages. The pupose of Numbering Gesture Recognition Application exists is to be basic for the next research to built translator sign languages to text. Android platform choosen because this platform already spread and open source, so it will be easily to spread this application.